Respostas
respondido por:
2
a) x³-x²-xy = x(x² -x -y)
b)a+b+(a+b)x ==> 1(a+b) +x(a+b) ==> (1+x)(a + b)
c)4x²-12x+9 ==> ( 2x - 3)²
dimitri10:
Nem lembrava dessas propriedades de multiplicação e nem me toquei no polinômio , rs.
respondido por:
1
a) x(x²-x-y)
b) a+b+ax+ bx
a + ax + b + bx
a(1+x) + b(1+x)
c)4x(x-3) + 9 ou 4x - 3(4x - 3)
b) a+b+ax+ bx
a + ax + b + bx
a(1+x) + b(1+x)
c)4x(x-3) + 9 ou 4x - 3(4x - 3)
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás